Destruction of Bakaloriškės - Zizas, Rimantas (Genocidas ir rezistencija, 2002)
The attack and merciless destruction (burning) of the village of Kaniūkai (Eišiškės district, Jašiūnai municipality) by the red army partisans on 29 January 1944, and the massacre of its people (38 people were killed in total in this village) was, unfortunately, not the only mass punitive (revengeful) action carried out by them in their fight against armed villages of south–eastern Lithuania, the so–called armed local self–defence. The red army partisans carried out a similar punitive violence of similar brutality during Easter 1944: on 12 April 1944, they burnt down the village of Bakaloriškės (about 40 homesteads in total) in the municipality of Onuškis, in the Trakai region, and terrorised and killed the inhabitants of this and other villages during the action.
Keywords: German occupation; Soviet partisans; terror